FINANCIAL REASONS FOR LIQUIDITY IN BUSINESS MANAGEMENT FOR DECISION MAKING - Herrera Freire, Alexander Geovanny (2016)
Financial liquidity indicators are fundamental to assess the economic and financial situation and a company ́s performance in the short term, that is, to detect if the company has sufficient financial resources and is available to cover the present obligations. The objective of this study is to analyze the financial ratios of liquidity as a strategy in business management for decision making. It is an analytical study based on the methodology of Gitman & Chad (2012) and of scientific journals which delimit the criterion of liquidity in a company as: “The liquidity represents the agility that the company has to cover its financial obligations in the short term”, according to Linares Mustaros, Farreras Noguer, Ferrer Comalat & Rabaseda Tares (2012); Marsano Delgado (2013) Morelos Gómez, Fontalvo Herrera & Hoz Granadillo (2012); Ochoa Ramirez & Toscano Moctezuma (2012) Vasquez Tejos (2010), among others. The importance of the financial management foundations is based on the ratios to improving the financial analysis and its business management. A correct analysis of the financial statements of the organization allows us to reach its current situation and enables to predict -within certain limits- its future development for decision making.